1994
DOI: 10.1159/000284866
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Lateralization in the Delusion of Substitution

Abstract: Five hundred and seventy cases in 252 reports of the delusion of substitution yielded 200 cases with an organic contributor to the occurrence of the delusion. In 79 cases lateralization or localization could be determined, with lesions primarily in the left temporal or right frontal areas. Factors related to ‘feature recognition’, ‘familiarity’ and ‘reduplication’ could be found and are discussed in relation to the neurobehavioral features of the symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…Of course, a subtle disconnection between IT and the limbic system of the kind we have postulated here would not be visible on a CT scan, but we are planning future imaging studies on this patient using fMRI and PET. Previous studies on Capgras patients have found lesions predominantly in the temporal (Signer 1994) and right fronto-parietal (Benson 1994) cortices, which is consistent with our two-lesion (ITlimbic, and right fronto-parietal) hypothesis.…”
Section: Lesion Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Of course, a subtle disconnection between IT and the limbic system of the kind we have postulated here would not be visible on a CT scan, but we are planning future imaging studies on this patient using fMRI and PET. Previous studies on Capgras patients have found lesions predominantly in the temporal (Signer 1994) and right fronto-parietal (Benson 1994) cortices, which is consistent with our two-lesion (ITlimbic, and right fronto-parietal) hypothesis.…”
Section: Lesion Analysissupporting
confidence: 92%
“…Ellis & Young (1990) adapted this approach to Capgras syndrome, making the ingenious suggestion that Capgras is a mirror image of prosopagnosia : damaged dorsal stream, intact ventral stream. There are several problems with this idea, however : (1) postcentral lesions in Capgras patients are more often located in the temporal lobes than in the occipital or parietal lobes (Signer 1994) ; (2) the dorsal visual stream primarily contains information from peripheral vision, whereas our visual interactions with people would seem to involve mainly focal vision, a ventral stream function ; (3) the ventral stream has dense reciprocal connections to the amygdala (Amaral et al 1992), which is strongly implicated in the skin conductance response (although apparently not necessary for it, Tranel & Damasio 1989 ;Lee et al 1989), whereas the dorsal stream does not ; (4) Some Capgras patients sometimes also have face-processing impairments (Young et al 1993), another ventral stream function. We propose instead that the principal cause of Capgras is a failure of communication between areas of ventral stream processing in the temporal lobe (e.g.…”
Section: Discussion : the Unbearable Likeness Of Beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Capgras' syndrome patients will sometimes even misidentify themselves as seen in photos, or even in a mirror (Hirstein & Ramachandran, 1997;Silva & Leong, 1994, review 30 cases of Capgras' for oneself). Capgras' syndrome fits the pattern of damage seen in the memory syndromes: damage to some knowledge system, in this case a perceptual one, paired with frontal damage (Signer, 1994).…”
Section: Capgras' Syndromementioning
confidence: 62%
“…But is this intended to cover both the first and second factors? The data from case studies tend to support a two-lesion theory of Capgras syndrome, with a more posterior lesion and a more frontal one (Signer, 1994).…”
Section: The Two-factor Approachmentioning
confidence: 67%